Crystals and their manufacturing method
Patent Information
- Application Number
- JP2021565667
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-20
- Filing Date
- 2020-12-18
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-12-18
AI Technical Summary
【0010】 本発明によれば、新規な結晶[新規な3-ヒドロキシ-N’-(1,3-ジメチルブチリデン)-2-ナフトエ酸ヒドラジドの結晶]を提供できる。
Smart Images

Figure 0007640469000004 
Figure 0007640469000005 
Figure 0007640469000006
Abstract
Description
[Technical field]
[0001] The present invention relates to novel crystals and the like. [Background technology]
[0002] 2. Description of the Related Art Various additives are used in rubber products such as tires. For example, hydrazide compounds are used as rubber additives (Patent Document 1, etc.). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-6845 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a novel crystal.
[0005] Another object of the present invention is to provide a novel method for producing crystals.
[0006] Another object of the present invention is to provide a novel rubber additive. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving the above problems, the present inventors focused on 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide and found that novel crystals of the compound can be obtained by appropriately selecting conditions for precipitating (i.e., crystallizing) the crystals.
[0008] Furthermore, the present inventors have found that among the novel crystals, each crystal imparts different physical properties to a rubber component when used as a rubber additive. Furthermore, the inventors have found that, among the above-mentioned novel crystals, the crystal of the present invention is particularly excellent in terms of low heat build-up and processability, and after further intensive investigations, they have completed the present invention.
[0009] That is, the present invention relates to the following inventions. [1] A crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide having a peak with maximum intensity at a diffraction angle (2θ) of 6.1±0.2° in a powder X-ray diffraction pattern. [2] A crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide having characteristic peaks at diffraction angles (2θ) of at least 6.1±0.2°, 17.7±0.2°, 17.9±0.2°, and 19.1±0.2° in a powder X-ray diffraction pattern. [3] The crystal according to the above-mentioned [2], having characteristic peaks at diffraction angles (2θ) of at least 6.1±0.2°, 17.7±0.2°, 17.9±0.2°, 18.2±0.2°, 19.1±0.2° and 23.8±0.2° in a powder X-ray diffraction pattern. [4] The crystal according to any one of the above [1] to [3], which has a melting point of 148° C. or higher. [5] A rubber additive comprising the crystals according to any one of the above [1] to [4]. [6] A rubber composition comprising the rubber additive according to [5] above. [7] A tire using the rubber composition described in [6] above. [8] A method for producing the crystal according to any one of the above [1] to [4], comprising a step of bubbling oxygen gas or an oxygen-containing gas into a solution containing 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide. [9] A method for improving low heat build-up and / or processability of rubber, using the crystals according to any one of the above items [1] to [4].
[10] Use of the crystal according to any one of the above [1] to [4] for improving low heat build-up and / or processability of rubber. Effect of the Invention
[0010] According to the present invention, a novel crystal (a novel crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide) can be provided.
[0011] Moreover, the present invention can provide a novel rubber additive containing the above crystals. Such rubber additives can impart low heat generation properties to the rubber component, and when used in a rubber composition, can provide a rubber product (such as a tire) that exhibits low heat generation properties.
[0012] Generally, when attempting to impart low heat generation properties to a rubber component, the processability tends to decrease, but the rubber additive of the present invention can achieve both low heat generation and processability.
[0013] The present invention also provides a novel method for producing crystals. [Brief description of the drawings]
[0014] [Figure 1] 1 shows the results of powder X-ray diffraction measurement of the crystals of Example 1. [Diagram 2] 1 shows the results of powder X-ray diffraction measurement of the crystals of Example 2. [Diagram 3] 1 shows the melting point measurement results of the crystals of Example 1. [Figure 4] 1 shows the melting point measurement results of the crystals of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] [crystal] The crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide of the present invention (hereinafter, sometimes simply referred to as the crystal of the present invention) may have a peak of maximum intensity at a diffraction angle (2θ) of, for example, 6.1° in a powder X-ray diffraction pattern analyzed by a powder X-ray diffractometer using Cu-Kα radiation (wavelength λ=1.54 Å) as shown in the Examples described later.
[0016] Furthermore, the crystals of the present invention may have characteristic peaks at diffraction angles (2θ), such as 6.1°, 17.7°, 17.9°, 18.2°, 19.1°, and 23.8°, in a powder X-ray diffraction pattern analyzed with a powder X-ray diffractometer using Cu-Kα radiation (wavelength λ=1.54 Å).
[0017] Furthermore, the crystals of the present invention may have characteristic peaks at diffraction angles (2θ) of at least 6.1°, 17.7°, 17.9°, and 19.1° in a powder X-ray diffraction pattern analyzed with a powder X-ray diffractometer using Cu-Kα radiation (wavelength λ=1.54 Å), or may have characteristic peaks at diffraction angles (2θ) of at least 6.1°, 17.7°, 17.9°, 18.2°, 19.1°, and 23.8°.
[0018] Generally, the diffraction angle (2θ) in powder X-ray diffraction may vary somewhat depending on the measurement conditions, and therefore, crystals in which the diffraction angle in powder X-ray diffraction coincides within the error range are also included in the crystals of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide of the present invention. The error of the diffraction angle may be, for example, ±0.2°. In other words, the crystals of the present invention also include those that coincide within the range of ±0.2° of each of the above diffraction angles, and in this specification, when a single numerical value is described as the diffraction angle, it is interpreted as being within the range of ±0.2° of that numerical value unless otherwise specified. In this specification, "diffraction angle 2θ±0.2°" means a diffraction angle within the range of (2θ-0.2°)≦2θ≦(2θ+0.2°), that is, within the range of (2θ-0.2°) to (2θ+0.2°). In addition, when two peak regions overlap, the two peaks may overlap. For example, the peak at 17.7° and the peak at 17.9° overlap in the peak region in the range of 17.7° to 17.9° in the range of "2θ±0.2°", but the two peaks may exist or overlap within the range of 17.7° to 17.9°.
[0019] Furthermore, the crystal of the present invention may have peaks at diffraction angles (2θ) of at least 17.7°, 17.9°, 18.2°, 19.1°, and 23.8°, each of which shows a peak intensity of 5% or more when the peak intensity at a diffraction angle (2θ) of 6.1° is taken as 100%.
[0020] Furthermore, the crystal of the present invention may have peaks at diffraction angles (2θ) of at least 17.7°, 17.9°, and 23.8°, each of which shows a peak intensity of 8% or more, when the peak intensity at a diffraction angle (2θ) of 6.1° is taken as 100%.
[0021] Furthermore, the crystal of the present invention may have a peak at a diffraction angle (2θ) of at least 17.9° that exhibits a peak intensity of 10% or more (e.g., 11 to 24%) when the peak intensity at a diffraction angle (2θ) of 6.1° is taken as 100%.
[0022] Furthermore, the crystal of the present invention may have a peak intensity at a diffraction angle (2θ) of 17.7° of 8 to 15% when the peak intensity at a diffraction angle (2θ) of 6.1° is taken as 100%.
[0023] The peak intensity itself may be different from that described above.
[0024] The melting point of the crystal of the present invention shows an endothermic peak at, for example, 147°C or higher, preferably 148°C or higher, more preferably 148 to 151°C, and even more preferably 148.5 to 150.5°C, in differential scanning calorimetry (DSC).
[0025] The form of the crystal of the present invention is not particularly limited, and may be an aggregate or a pulverized product obtained by appropriate pulverization.
[0026] The average particle size of the crystals of the present invention is not particularly limited, but is preferably the particle size at 50% of the cumulative value calculated by the number conversion method (average particle size D 50 ) may be, for example, 0.5 μm or more, preferably 5 to 50 μm, and more preferably 10 to 30 μm. When the crystals are aggregates, the size may be adjusted to fall within the above range by an appropriate operation such as pulverization.
[0027] The average particle size of the crystals of the present invention is, when the crystals are pulverized, an average particle size D 50 However, it may be, for example, 0.5 μm or more, preferably 5 to 50 μm, and more preferably 10 to 30 μm.
[0028] Average particle size D 50 The method for measuring is not particularly limited, and may be, for example, the method described in the Examples below.
[0029] The specific surface area of the crystal of the present invention is not particularly limited, but is, for example, 0.4 to 3.0 m 2 / g, preferably 0.5 to 2.5 m 2 / g, more preferably 0.8 to 1.4 m 2 / g.
[0030] The method for measuring the specific surface area is not particularly limited, and may be, for example, the method described in the Examples below.
[0031] The shape of the crystal of the present invention is not particularly limited and may be, for example, plate-like, columnar, needle-like, etc., and is preferably plate-like. The crystal of the present invention may include other crystals (other crystal polymorphs) of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide within the scope of the present invention.
[0032] The crystals of the present invention can be obtained, for example, by the production method described below.
[0033] [Manufacturing method] The crystals of the present invention can be produced through a process of contacting a solution containing 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide (hereinafter, sometimes simply referred to as "Compound A") (hereinafter, sometimes simply referred to as "Compound A solution") with oxygen (hereinafter, sometimes referred to as "contact process").
[0034] The solution of compound A may be a solution in which compound A is dissolved in a solvent, and may be a reaction solution in which compound A is produced. Examples of the solvent for dissolving compound A include alcohols (e.g., isopropyl alcohol, butanol, etc.), hydrocarbons (e.g., heptane, toluene, etc.), esters (e.g., butyl acetate, etc.), methyl isobutyl ketone, etc., and a mixed solvent of one or more of these may be used.
[0035] The reaction solution used to produce compound A may be, for example, a reaction solution used to produce compound A from 3-hydroxy-2-naphthoic acid hydrazide and methyl isobutyl ketone, which are raw material compounds for compound A.
[0036] Examples of the solvent used in the reaction include alcohols (e.g., isopropyl alcohol, butanol, etc.), hydrocarbons (e.g., heptane, toluene, etc.), esters (e.g., butyl acetate, etc.), methyl isobutyl ketone, etc., and a mixed solvent of one or more of these can be used. However, it is preferable to use methyl isobutyl ketone, which is a reaction raw material, as the solvent.
[0037] The content (concentration) of compound A in the solution of compound A is, for example, 20% by mass or more, preferably 25% by mass or more, and more preferably 30% by mass or more. In order to efficiently obtain the crystal of the present invention, the concentration of compound A in the solution may be, for example, 50% by mass or less, preferably 35% by mass or less.
[0038] The solution of compound A is preferably heated to usually 70° C. or higher, preferably 75° C. or higher, and more preferably 80° C. or higher, to completely dissolve compound A. The reaction for producing compound A from 3-hydroxy-2-naphthoic acid hydrazide and methyl isobutyl ketone is carried out under heated conditions, and therefore the reaction solution can be used as it is as a solution of compound A. In particular, when the solvent for the reaction is methyl isobutyl ketone, it is suitable as a solution of compound A because it is heated to 110° C. or higher.
[0039] The oxygen to be contacted with the solution of compound A is not particularly limited, and may be in a gaseous state or a liquid state, but it is preferable to use the gaseous state. Examples of the gaseous oxygen include oxygen gas and oxygen-containing gas (e.g., a mixed gas with an inert gas such as argon-oxygen mixed gas, air, etc.), and air is preferable from the viewpoint of ease of handling and economy.
[0040] The method for contacting the solution of compound A with oxygen is not particularly limited as long as the contact occurs at the interface between oxygen and the solution, and examples of the method include a method in which the solution of compound A is allowed to stand or is stirred in the presence of oxygen gas or an oxygen-containing gas, and a method in which oxygen gas or an oxygen-containing gas is introduced into the solution of compound A and bubbled therein. From the viewpoint of efficient contact with oxygen, the method in which oxygen gas or an oxygen-containing gas is introduced into the solution of compound A and bubbled therein is preferred. That is, the present invention encompasses a method for producing a crystal of compound A, which comprises a step of bubbling oxygen gas or an oxygen-containing gas into a solution of compound A, and more specifically, includes a method for producing a crystal of compound A, which comprises a step of bubbling oxygen gas or an oxygen-containing gas into a solution of compound A, followed by crystallization.
[0041] In the contact step, the amount of oxygen used is not particularly limited and may be, for example, 0.001 mole or more, preferably 0.01 mole or more, relative to 1 mole of compound A, with no particular upper limit.
[0042] The time for contacting the solution of compound A with oxygen is usually 0.1 hours or more, preferably 0.5 hours or more, more preferably 1 hour or more, and may be, for example, 72 hours or less, preferably 48 hours or less, more preferably 24 hours or less. When contacting by bubbling, it is expected that the solvent of the solution may evaporate, so it is preferable to stop bubbling and combine it with a method of leaving the solution standing or stirring.
[0043] In addition, if the contacting step is carried out at a temperature near the boiling point of the solvent in the solution of compound A, evaporation of the solvent may prevent contact with oxygen. Therefore, the contacting step is preferably carried out at a temperature lower than that temperature. However, it is preferable to maintain the state in which compound A is completely dissolved, and the temperature may be appropriately set to usually 70°C or higher, preferably 75°C or higher, and more preferably 80°C or higher.
[0044] It is preferable to precipitate (or crystallize or crystallize) the crystals promptly after the contact step is completed. If precipitation of crystals is observed during the contact step, it is preferable to heat the mixture again after the contact step to dissolve the precipitated crystals and then crystallize the mixture in order to obtain the crystals of the present invention with high purity.
[0045] The crystallization method may be a method in which a poor solvent is added to a solution of compound A to precipitate crystals, or a method in which a solution of compound A is cooled to precipitate crystals.
[0046] In the method of precipitating crystals by adding a poor solvent to a solution of compound A, the poor solvent to be used may be any solvent that can precipitate crystals from the solution of compound A, and examples of the poor solvent include ether solvents [e.g., diethyl ether, diisopropyl ether, tetrahydrofuran (THF), 1,4-dioxane, etc.], aliphatic or alicyclic hydrocarbon solvents (e.g., pentane, hexane, cyclohexane, petroleum ether, etc.), etc., which may be used alone or in combination of two or more kinds. The amount of the poor solvent used varies depending on the type and amount of the solvent used in the solution of compound A, as well as conditions such as temperature, and can be appropriately set while checking the crystallization state.
[0047] In the method of precipitating crystals by cooling a solution of compound A, the cooling rate is not particularly limited, but may be, for example, 0.5 to 30° C. / min, preferably 0.5 to 20° C. / min, and more preferably 0.5 to 10° C. / min, from the viewpoint of efficiently obtaining crystals. The cooling temperature is not particularly limited, and may be, for example, 40° C. or lower, 30° C. or lower, preferably 15° C. or lower, and more preferably 10° C. or lower, and aging may be carried out at this temperature.
[0048] The aging may be, for example, an operation of stirring or leaving a solution of compound A without adding other components, and the aging time is not particularly limited and may be, for example, 0.1 minutes to 3 hours, preferably 1 minute to 1 hour, and more preferably 5 to 30 minutes.
[0049] As a crystallization method, a method in which a solution of compound A is cooled to precipitate crystals is preferred from the viewpoints of operational efficiency, cost, purity of the obtained crystals, and the like.
[0050] The crystallization may be carried out by adding seed crystals of compound A. The seed crystals may be separately prepared in advance using the production method of the present invention.
[0051] The proportion of seed crystals added is not particularly limited, and may be 10% by mass or less (for example, 0.05 to 10% by mass, 0.1 to 8% by mass, 0.1 to 5% by mass) of the substrate (compound A).
[0052] The crystals obtained by the above production method may be isolated by a general solid-liquid separation operation (eg, filtration, centrifugation, etc.).
[0053] The use of the crystals of the present invention obtained as described above is not particularly limited, but they may be suitably used, in particular, as an additive for rubber.
[0054] Therefore, the present invention includes a rubber additive containing the crystal of the present invention.
[0055] The rubber additive of the present invention may be used in any application, but may be particularly suitable for use in rubber compositions.
[0056] Therefore, the present invention includes a rubber composition containing the rubber additive of the present invention. Such a rubber composition can also be said to be a composition containing the crystal of the present invention (or compound A containing the crystal of the present invention). The rubber composition of the present invention is only required to contain at least the crystals of the present invention, and may contain crystals other than the crystals of the present invention within the scope of the present invention. The proportion of the crystals of the present invention in compound A is not particularly limited, and may be, for example, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, etc.
[0057] [Rubber composition] The rubber composition may include a rubber component. The rubber component is not particularly limited, and examples thereof include diene rubbers (e.g., polybutadiene rubber, isoprene rubber, styrene butadiene rubber, styrene isoprene butadiene rubber, chloroprene rubber, acrylonitrile butadiene rubber, etc.), non-diene rubbers (e.g., ethylene propylene rubber, butyl rubber, etc.), etc. The rubber component may be either natural rubber or synthetic rubber. The rubber components may be used alone or in combination of two or more.
[0058] The rubber component contained in the rubber composition of the present invention preferably contains a diene rubber, and among these, it is particularly preferable to use natural rubber. The content of the diene rubber in the rubber component is not particularly limited, but from the viewpoint of maintaining excellent low heat buildup, it is preferably 80% by mass or more, and more preferably 90% by mass or more.
[0059] The rubber composition of the present invention may contain additives other than the rubber additive of the present invention. The other additives are not particularly limited and may be additives commonly used in the rubber industry. Examples of other additives include antioxidants (e.g., hydrazide compounds other than compound A, phenol-based antioxidants, imidazole-based antioxidants, amine-based antioxidants, etc.), fillers {e.g., inorganic fillers [e.g., white fillers (e.g., silica, silicates, carbonates, metal oxides, etc.)], organic fillers (e.g., carbon black, etc.)}, vulcanizing agents (e.g., sulfur, etc.), process oils (e.g., paraffin-based process oils, naphthene-based process oils, aromatic process oils, etc.), vulcanization accelerators (e.g., thiazole-based vulcanization accelerators, sulfenamide-based vulcanization accelerators, etc.), vulcanization accelerator assistants [e.g., zinc oxide, fatty acids (e.g., stearic acid, etc.)], antioxidants, antiozonants, and silane coupling agents. The other additives may be used alone or in combination of two or more.
[0060] In the rubber composition, the proportion of the rubber additive of the present invention (or the crystal of the present invention, or compound A containing the crystal of the present invention) is not particularly limited, but from the viewpoints of low heat buildup, processability, etc., it may be, for example, 0.05 to 30 parts by mass, preferably 0.05 to 10 parts by mass, and more preferably 0.05 to 5 parts by mass, per 100 parts by mass of the rubber component.
[0061] In addition, the proportion of the rubber additive of the present invention (or the crystal of the present invention, or compound A containing the crystal of the present invention) in the rubber composition is not particularly limited, but from the viewpoints of low heat buildup, processability, etc., it may be, for example, 0.02 to 18 mass%, preferably 0.02 to 6 mass%, and more preferably 0.02 to 3 mass% based on the total amount of the rubber composition.
[0062] The content of the rubber component in the rubber composition of the present invention is appropriately set depending on the intended use of the rubber composition. For example, when the rubber composition is used for the purpose of maintaining the elasticity of the rubber without reducing it, the content of the rubber component in 100% by mass of the rubber composition is preferably 30 to 99% by mass, and more preferably 40 to 80% by mass.
[0063] (Filler) The rubber composition of the present invention usually contains a filler as another additive, in addition to the above-mentioned rubber component. By including a filler together with the rubber component and the crystals of the present invention, the dispersibility of the filler is improved, and performance such as strength and abrasion resistance can be maintained at a high level, while achieving excellent low heat build-up even when a filler is included.
[0064] Here, the content of the filler is not particularly limited, but is preferably 10 to 160 parts by mass, and more preferably 30 to 100 parts by mass, relative to 100 parts by mass of the rubber component. By optimizing the amount of the filler, better low heat buildup properties and abrasion resistance can be achieved, and when the content is 10 parts by mass or more, sufficient abrasion resistance can be obtained, and when the content is 160 parts by mass or less, deterioration of low heat buildup properties can be suppressed. In addition, in the rubber composition, the content of the filler is not particularly limited, but from the viewpoint of low heat generation, abrasion resistance, and the like, it may be, for example, 1,000 to 16,000 parts by mass, preferably 2,000 to 10,000 parts by mass, and more preferably 3,000 to 7,000 parts by mass (for example, 4,000 to 6,000 parts by mass, etc.) per 100 parts by mass of the rubber additive of the present invention (or the crystal of the present invention, or compound A containing the crystal of the present invention).
[0065] The type of the filler is not particularly limited and may be any of the above-mentioned exemplified ones (e.g., carbon black, silica, etc.). Among them, it is preferable to contain carbon black from the viewpoint of realizing superior low heat generation properties and improving abrasion resistance. Examples of the carbon black include GPF, FEF, SRF, HAF, ISAF, IISAF, and SAF grade carbon black.
[0066] From the viewpoint of obtaining better abrasion resistance, the content of the carbon black is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 50 parts by mass or more, per 100 parts by mass of the rubber component. From the viewpoint of improving low heat build-up properties and processability while maintaining a high level of abrasion resistance, the content of the carbon black is preferably 160 parts by mass or less, more preferably 90 parts by mass or less, and even more preferably 70 parts by mass or less, per 100 parts by mass of the rubber component. Carbon black tends to deteriorate low heat buildup and processability, but the crystals of the present invention can achieve both low heat buildup and processability, so that a relatively large amount of carbon black can be contained. In addition, since the crystals of the present invention can contain a relatively large amount of carbon black, the fracture resistance of the rubber can be further improved.
[0067] The silica used as the filler is not particularly limited, and for example, wet silica, dry silica, colloidal silica, etc. can be used.
[0068] As the inorganic filler, for example, an inorganic compound represented by the following formula (I) can also be used. nM xSiO Y zH2O Formula (I) (In the formula, M is at least one selected from the group consisting of metals selected from the group consisting of Al, Mg, Ti, Ca, and Zr, oxides or hydroxides of these metals, and hydrates thereof, and carbonates of these metals; and n, x, y, and z are integers of 1 to 5, 0 to 10, 2 to 5, and 0 to 10, respectively.)
[0069] Inorganic compounds of the above formula (I) include alumina (Al2O3) such as γ-alumina and α-alumina; alumina monohydrate (Al2O3·H2O) such as boehmite and diaspore; aluminum hydroxide [Al(OH)3] such as gibbsite and bayerite; aluminum carbonate [Al2(CO3)3], magnesium hydroxide [Mg(OH)2], magnesium oxide (MgO), magnesium carbonate (MgCO3), talc (3MgO·4SiO2·H2O), attapulgite (5MgO·8SiO2·9H2O), titanium white (TiO2), titanium black (TiO 2n-1 ), calcium oxide (CaO), calcium hydroxide [Ca(OH)2], magnesium aluminum oxide (MgO·Al2O3), clay (Al2O3·2SiO2), kaolin (Al2O3·2SiO2·2H2O), pyrophyllite (Al2O3·4SiO2·H2O), bentonite (Al2O3·4SiO2·2H2O), aluminum silicate (Al2SiO5, Al4·3SiO4·5H2O, etc.), magnesium silicate (Mg2SiO4, MgSi O3, etc.), calcium silicate (Ca2SiO4, etc.), calcium aluminum silicate (Al2O3·CaO·2SiO2, etc.), calcium magnesium silicate (CaMgSiO4), calcium carbonate (CaCO3), zirconium oxide (ZrO2), zirconium hydroxide [ZrO(OH)2·nH2O], zirconium carbonate [Zr(CO3)2], various zeolites, and crystalline aluminosilicates containing alkali metals or alkaline earth metals, etc. can be mentioned.
[0070] The method for producing the rubber composition is not particularly limited, and for example, each component contained in the rubber composition may be kneaded. The kneading method is not particularly limited, and a conventional method may be used, and a kneader (for example, a roll, an internal mixer, a Banbury mixer, etc.) may be used.
[0071] The order in which the components in the rubber composition are kneaded is not particularly limited. For example, all the components may be kneaded at once, or any one of the components may be kneaded in advance and then the remaining components may be kneaded.
[0072] The rubber composition of the present invention can be vulcanized to obtain a rubber. The vulcanization method is not particularly limited, and a conventional method may be used.
[0073] The use of the rubber is not particularly limited, but it may be particularly suitable for use in tires (for example, tread components, shoulder components, sidewall components, bead components, carcass components, etc.).
[0074] Therefore, the present invention also includes a tire (for example, a pneumatic tire) using the rubber composition. The method for manufacturing the tire is not particularly limited, and a conventional method may be used. EXAMPLES
[0075] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these.
[0076] (Powder X-ray diffraction measurement) The crystal structure was measured using an X-ray diffraction measurement device (Rigaku, Ultima IV) with an X-ray tube of Cu (wavelength λ=1.54059 Å), tube voltage of 40 kV, tube current of 40 mA, sampling width of 0.02°, and a scan speed of 30° / min.
[0077] (Melting Point) The melting point of the crystals was calculated from the appearance temperature of an endothermic peak observed when the temperature was increased from 50°C to 170°C at a heating rate of 10°C / min under a nitrogen stream using a differential scanning calorimeter (DSC6200, manufactured by Seiko Instruments Inc.).
[0078] (Average particle size D 50 ) The average particle size of the crystals was measured using a laser diffraction particle size distribution analyzer "HELOS&RODOS" manufactured by Sympatec, and was calculated as the particle size at 50% of the sieve cumulative distribution, i.e., D 50 was measured.
[0079] (specific surface area) The specific surface area of the crystal was measured by the BET method using a "TriStar II" manufactured by Micromeritics.
[0080] Example 1 200 mL of methyl isobutyl ketone and 35 g of 3-hydroxy-2-naphthoic acid hydrazide (HNH) were charged into a reactor equipped with a Dean-Stark type reflux condenser and a stirrer, and the mixture was heated to about 116°C (HNH concentration: 17.9% by mass), and heated under reflux for 4 hours while removing the distilled water. The reaction solution was then cooled to 100°C, and stirred at 250 rpm for 3 hours while blowing air into the reaction solution with an air pump. The reaction solution was cooled at a cooling rate of 0.8°C / min while stirring at 250 rpm, and after confirming that nuclei had precipitated at 35°C, it was quickly cooled to 10°C, and the precipitated crystals were filtered off and dried under reduced pressure to obtain slightly brown crystals (a-1). The obtained crystal (a-1) had a melting point of 148.7°C (Figure 3) and a specific surface area of 1.04 m 2 / g, average particle size D 50 The diameter was 15.3 μm and the particles were plate-shaped. The results of powder X-ray diffraction measurement of the obtained crystals (a-1) are shown in FIG.
[0081] [Table 1]
[0082] Example 2 200 mL of methyl isobutyl ketone and 35 g of 3-hydroxy-2-naphthoic acid hydrazide (HNH) were charged into a reactor equipped with a Dean-Stark type reflux condenser and a stirrer, and the mixture was heated to about 116 ° C. (HNH concentration: 17.9 mass%) and refluxed for 4 hours while removing the distilled water. The reaction solution was then cooled to 80 ° C. and stirred at 250 rpm for 3 hours while blowing air into the reaction solution with an air pump. The reaction solution was then held at the same temperature in the presence of air for 21 hours. The reaction solution was cooled at a cooling rate of 5.5 ° C. / min while stirring at 250 rpm, and after confirming that nuclei had precipitated at 35 ° C., it was quickly cooled to 10 ° C., and the precipitated crystals were filtered and dried under reduced pressure to obtain slightly brown crystals (a-2). The resulting crystal (a-2) had a melting point of 148.8°C (Figure 4) and a specific surface area of 1.21 m 2 / g, average particle size D 50 The particle size was 11.8 μm and was plate-shaped.
[0083] The results of powder X-ray diffraction measurement of the crystals obtained in Example 2 are shown in FIG.
[0084] [Table 2]
[0085] As shown in FIG. 1 and Table 1, the crystal (a-1) of Example 1 exhibited a peak with the maximum intensity at 6.1°. Furthermore, the crystal (a-1) of Example 1 exhibited characteristic peaks at 6.1°, 17.7°, 17.9°, 18.2°, 19.1°, and 23.8°.
[0086] As shown in FIG. 2 and Table 2, the crystal (a-2) of Example 2 also showed a peak of maximum intensity at 6.1°, and characteristic peaks at 6.1°, 17.7°, 17.9°, 18.2°, 19.1°, and 23.8°.
[0087] (Reference example 1) A reactor equipped with a Dean-Stark type reflux condenser and a stirrer was charged with 24 ml of methyl isobutyl ketone, 126 ml of methanol, and 33.0 g of 3-hydroxy-2-naphthoic acid hydrazide (HNH concentration: 21.7% by mass), heated to about 64°C, and heated under reflux for 6 hours. The reaction solution was cooled to 20°C at a cooling rate of 1.3°C / min, and after confirming that crystals had precipitated, the solution was aged at about 20°C for 12 hours. The precipitated crystals were filtered and dried under reduced pressure to obtain pale yellow crystals (b). The obtained crystals (b) were not the crystals of the present invention. The obtained crystal (b) has a melting point of 160.1°C and a specific surface area of 0.9 m 2 / g, average particle size D 50 The diameter was 11.7 μm and the shape was columnar.
[0088] Rubber composition and method for producing rubber Each component shown in step (I) in Table 3 below was mixed in the ratio (parts by mass) and kneaded for 3 minutes in a Banbury mixer while adjusting the rotation speed so that the maximum temperature of the mixture was 150° C. After curing until the temperature of the mixture was 80° C. or less, each component shown in step (II) in Table 3 was added in the ratio (parts by mass) and kneaded while adjusting the maximum temperature of the mixture to 110° C. or less to produce each unvulcanized rubber composition. The unvulcanized rubber composition obtained here was heated at 150° C. for 30 minutes using a vulcanizing press to obtain each rubber.
[0089] Low heat generation (low heat generation index) test The rubber of Compounding Example 1 was measured for Tan δ value using a viscoelasticity measuring device (manufactured by Metravib) under the conditions of temperature 40°C, dynamic strain 5%, and frequency 15Hz. The rubber of Reference Compounding Example 1 was also measured for Tan δ value under the above conditions. In addition, for the rubber of Comparative Compounding Example 1, the Tan δ value was measured under the above conditions, and the Tan δ value was set to 100. The low heat build-up index was calculated based on the following formula and is shown in Table 3. Note that a smaller low heat build-up index value indicates lower heat build-up and smaller hysteresis loss. Formula: Low heat index = {(Tan δ value of each rubber in Compounding Example 1 or Reference Compounding Example 1) / (Tan δ value of rubber in Comparative Compounding Example 1)} × 100
[0090] Mooney Viscosity (Processability Index) Test The Mooney viscosity of the unvulcanized rubber compositions of Compounding Example 1 and Reference Compounding Example 1 was measured at 100°C using a Mooney viscometer. The Mooney viscosity of the unvulcanized rubber composition of Comparative Compounding Example 1 was measured in the same manner as above, and the Mooney viscosity was set to 100. The processability index was calculated based on the following formula and shown in Table 3. The smaller the processability index value, the better the processability and the better the productivity of the unvulcanized rubber composition. Formula: Processability index = {(Mooney viscosity of the unvulcanized rubber composition of Compounding Example 1 or Reference Compounding Example 1) / (Mooney viscosity of the unvulcanized rubber composition of Comparative Compounding Example 1)} × 100
[0091] [Table 3] *1: NR: Natural rubber TSR20 *2: CB (carbon black); Cabot Corporation, N234 *3: Antioxidant (N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine); manufactured by Kemai Chemical Co., Ltd. *4: Wax; Rhein Chemie Rheinau, Antilux 111 *5: Stearic acid; manufactured by Sichuan Tianyu Grease Co., Ltd. *6: Crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide obtained in Example 1 *7: Crystals of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide obtained in Reference Example 1 *8: Vulcanization accelerator (TBBS); N-(tert-butyl)-2-benzothiazole sulfenamide (Ouchi Shinko Chemical Industry Co., Ltd., Sancera-NS-G) *9: Sulfur; manufactured by Shanghai Jinghai Chemical Co., Ltd. *10: Zinc oxide; manufactured by Dalian Zinc Oxide Co., Ltd.
[0092] As the above results show, the rubber of Compounding Example 1, in which the crystals (a-1) were added, had excellent low heat build-up properties compared to the rubber of Comparative Compounding Example 1, in which no crystals of Compound A were added. In addition, it was revealed that when used as a rubber additive, the crystal (a-1) of Compounding Example 1 has superior low heat generation and processability compared to another new crystal, the crystal (b) of Reference Compounding Example 1. [Industrial Applicability]
[0093] The crystals of the present invention are extremely useful industrially since they can be used as a rubber additive capable of imparting low heat generation properties to rubber components without impairing processability.
Claims
1. A crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide having a peak with maximum intensity at a diffraction angle (2θ) of 6.1±0.2° in a powder X-ray diffraction pattern.
2. A crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide having characteristic peaks at diffraction angles (2θ) of at least 6.1±0.2°, 17.7±0.2°, 17.9±0.2° and 19.1±0.2° in a powder X-ray diffraction pattern.
3. The crystal according to claim 2, having characteristic peaks at diffraction angles (2θ) of at least 6.1±0.2°, 17.7±0.2°, 17.9±0.2°, 18.2±0.2°, 19.1±0.2° and 23.8±0.2° in a powder X-ray diffraction pattern.
4. The crystal according to any one of claims 1 to 3, having a melting point of 148°C or higher.
5. A rubber additive comprising the crystal according to any one of claims 1 to 4.
6. A rubber composition comprising the crystals described in any one of claims 1 to 4.
7. A rubber composition comprising the crystals described in any one of claims 1 to 4 and a filler.
8. The rubber composition according to claim 7, wherein the filler content is 1,000 to 16,000 parts by mass per 100 parts by mass of the crystals.
9. A tire using the rubber composition according to any one of claims 6 to 8.
10. A method for producing the crystal according to any one of claims 1 to 4, comprising a step of bubbling oxygen gas or an oxygen-containing gas into a solution containing 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide.
11. A method for improving low heat build-up and / or processability of rubber by using the crystals according to any one of claims 1 to 4.
Citation Information
Patent Citations
Pneumatic tire
JP1998330549A
Hydrazone derivative
JP1999292834A
Rubber composition and tire using the same
JP2019006845A
Rubber composition and pneumatic tires
WO1998044040A1
Rubber composition and tire
WO2019235526A1